Paediatric Strategy Forum for medicinal product development for acute myeloid leukaemia in children and adolescents: ACCELERATE in collaboration with the European Medicines Agency with participation of the Food and Drug Administration. (September 2020) - Pearson, Andrew D.J.; Zwaan, C.Michel; Kolb, E.Anders; Karres, Dominik; Guillot, Julie; Kim, Su Young; Marshall, Lynley; Tasian, Sarah K.; Smith, Malcolm; Cooper, Todd; Adamson, Peter C.; Barry, Elly; et al.
Abstract: Purpose: The current standard-of-care for front-line therapy for acute myeloid leukaemia (AML) is a combination of an anthracycline with cytarabine resulting in significant short-term and long-term toxicity, but still approximately 40% of children relapse. Therefore, there is a major need to accelerate the introduction of innovative medicines into the therapy, yet drug development continues to be adult-focused. Furthermore, there are major differences, including differing profiles of genetic abnormalities, making clinical development of adult AML drugs in children problematic. The large number of competing agents in rare patient populations requires coordinated prioritisation, within the global regulatory framework and cooperative group initiatives. Methods: To address these issues, the fourth multi-stakeholder Paediatric Strategy Forum focused on AML in children and adolescents. Results: Eight classes of medicinal products were discussed at the Forum: FLT3, IDH1&2, checkpoint, cell signalling and HDAC inhibitors, monoclonal antibodies, bispecific T cell engagers and ADCs as well as other cytotoxics. CD123 is a high priority target for immunotherapies, and the paediatric development of CD123-targeted drugs should be accelerated as a proof-of-concept. Efforts must be coordinated, however, as there are a limited number of studies that can be delivered. The studies of FLT3 inhibitors included in agreed paediatric investigation plans (PIPs) present challenges to be completed because they would require enrolment of a larger number of patients than actually exist. A consensus was developed by industry and academia of optimised clinical trials, which could be included in PIPs. For AML with rare mutations that are more frequent in adolescents than in children, adult trials should enrol adolescents and when scientifically justified, efficacy data could be extrapolated from adolescent and adult data to younger children. There is also an important need to standardise internationally and validate methodologies and definitions of minimal residual disease, so that it can be used as a new response criterion. Industry supported, academic sponsored platform trials with compounds from different pharmaceutical companies could identify products to be further developed in paediatric AML. The Leukaemia and Lymphoma Society PedAL/EUpAL initiative may fulfil these requirements and has the potential to be a major advance in the field. Conclusion: The initiatives created during the Forums will be continued as part of an ongoing process, aiming to accelerate drug development for children with AML and ultimately improve clinical outcomes. Highlights: Introduction of innovative medicines into paediatric acute myeloid leukaemia (AML) needs to be accelerated. Trials of new agents in de novo  AML should be embedded in cooperative group trials. Prioritisation is required, as there are a limited number of deliverable studies. The PedAL/EUpAL Master Trial should accelerate the evaluation of novel drugs. Development of CD123-targeted drugs should be accelerated as a proof-of-concept.